2019
DOI: 10.1155/2019/1769374
|View full text |Cite
|
Sign up to set email alerts
|

HuoXueTongFu Formula Alleviates Intraperitoneal Adhesion by Regulating Macrophage Polarization and the SOCS/JAK2/STAT/PPAR-γ Signalling Pathway

Abstract: Intraperitoneal adhesion is a common complication after abdominal surgery, which seriously affects the quality of life of patients. HuoXueTongFu Formula (HXTF) plays an important role in the prevention and treatment of intraperitoneal adhesions. However, the molecular-related mechanisms are still not fully known. In this study, the model of Intrapetitoneal adhesion was established by cecum abrasion and treated with HXTF for one week. RAW264.7 cells were given LPS, IFN-γ, IL-4, HXTF-medicated serum, and PPAR-γ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…Since this is the first study to validate that Sart1 can modulate macrophage polarization, we attempted to unmask the underlying mechanism. Previous studies have demonstrated that the STAT6/PPAR-γ signaling pathway is essential for macrophage polarization 32 , 36 . Therefore, the expression levels of p-STAT6 and PPAR-γ were evaluated in gain and loss-of-function assays.…”
Section: Discussionmentioning
confidence: 99%
“…Since this is the first study to validate that Sart1 can modulate macrophage polarization, we attempted to unmask the underlying mechanism. Previous studies have demonstrated that the STAT6/PPAR-γ signaling pathway is essential for macrophage polarization 32 , 36 . Therefore, the expression levels of p-STAT6 and PPAR-γ were evaluated in gain and loss-of-function assays.…”
Section: Discussionmentioning
confidence: 99%
“…The PPA model was prepared as previous study reported [26] [27] . In brief, all rats were fasted for 12 h but allowed to drink water before the experiment.…”
Section: Animal Model Preparation and Group Assignmentmentioning
confidence: 99%
“…The degree of adhesion was determined using a five-stage adhesion score system [ 13 , 24 , 25 ] by two independent investigators in a blinded way. This scoring system included five stages adhesion scores ranging from 0 to 4.…”
Section: Methodsmentioning
confidence: 99%